Oral Squamous Cell Cancer Scenario in a Tertiary Hospital in Western Region of Nepal - Bajgai, Dwarika Prasad; Agrawal, Bela; Lamichhane, Narayan Sharma (Journal of Nepalgunj Medical College, 2021)
Introduction: Oral squamous cell cancer involves oral subsites namely lip, buccal mucosa, gingivobuccal sulcus, mandible, retromolar trigone, tongue, floor of the mouth, maxilla and hard palate. It has multifactorial etiologies. Alcohol, tobacco chewing, smoking, betel quid chewing, trauma and HPV viruses are implicated as the predisposing factors of oral squamous cell carcinoma. If detected early, oral cavity cancer is easily preventable and curable. Aims: To evaluate oral squamous cell cancer demographics, as well as risk factors, site, grades, and stages. Methods: This prospective cross-sectional descriptive type of study was done in patients attending dental outdoor patient department of Nepalgunj medical college from July 2018 to August 2020. 46 patients selected by enumerative sampling method in the study after they were histopathologically confirmed with oral squamous cell carcinoma by biopsy. All included patients were having primary oral cancer, single, unilateral and untreated. After data collection current oral squamous cell cancer demographics, as well as risk factors, site, grades, and stages were established. Results: Out of 46 patients ranging from 32 to 79 years 28(60.8%) were males and 18(39.1%) were females with mean age range of 55.41 ± 10.84 years. 26(56.5%) of total displayed oral squamous cell carcinoma at buccal mucosa. 25(54.3%) of total consumed gutkha and paan with betel nut plus tobacco. 30(65.2%) of total were exposed to carcinogen for a period of 21-40 years. 32(69.5%) of total had well differentiated oral squamous cancer. 32(69.5%) of total were at stage III at the time of presentation. Conclusion: Oral cancer occurred more in males, at buccal mucosa and in people above 51 years, and in those who consumed gutka and paan, betel nut plus tobacco. It was also more in people with longer history of exposure to carcinogens.